Fertility in Germany before and after the 2011 Census: Still no trend reversal in sight. - Pötzsch, Olga (Bundesinstitut für Bevölkerungsforschung, 2016)
The population projections by the German Federal Statistical Office show a likely decrease in the number of births in the 2020s. This development will be the result of a declining number of prospective mothers combined with an assumed continued low fertility rate. Given the available empirical findings prior to the 2011 census, there was no indication that a possible distinct rise in the fertility rate in the next decade would compensate for the declining number of potential mothers. However, the 2011 census led to revisions in the population size, age structure and consequently in relative fertility measures such as period and cohort fertility rates. The objective of this article is to quantify the effects of the 2011 census on these fertility statistics and to check the validity of previous findings for fertility trends on the census-adjusted data basis. A special focus is laid on analyses of the cohort fertility and the consequences of ever-later entry into motherhood on the completed fertility and on parity distribution. Using numerous findings, we will show that a continuous rise in the completed fertility in the coming two decades cannot be realised without a reversal of fertility behaviour. A greater increase in fertility from the age of 30 onwards would be necessary to offset the decrease in fertility for ages under 30 - a trend which intensified with cohort 1974 - and thereby stabilise the total cohort fertility rate at a relatively low level between 1.5 and 1.6 births per woman. A rise and subsequent stabilisation of the total cohort fertility rate at the level of at least 1.6 births per woman would, additionally, necessitate a trend reversal in the development of childlessness and distinct changes in birth timing.
Keywords: Bevölkerungsentwicklung; Bevölkerungsprognose; Generatives Verhalten; Lebensalter; Geburtenrate; Fertilität; Kinderlosigkeit; Bevölkerungsvorausberechnung; Datengrundlage